Challenges faced by medical faculty in implementation of competency-based medical education and lessons learned - Apurva Agrawal; Ashish Sharma; Anita Sharma; Charusmita Agrawal (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Regulations on Graduate Medical Education (Amendment), 2019 (GME) introduced competency-based medical education (CMBE) for undergraduate medical students and were implemented in the 2019 entrance batch in medical colleges all over India. This study aimed to find out the challenges faced by medical teachers in CBME implementation, lessons learned, and the level of preparedness for upcoming batches. MATERIAL AND METHODS: A cross-sectional, multi-centric descriptive study was conducted from November 2021 to February 2022 including first-year faculty of medical colleges. A self-administered questionnaire was provided through electronic media, about challenges faced during CBME implementation and suggestions for improvement. Responses were analyzed as descriptive statistics, and content analysis was conducted for open-ended questions. RESULTS: A total of 50 responses were analyzed. About 46% believed that the foundation course (FC) could satisfy the GME Regulation's goal to only some extent. About 60% believed that integration was not optimum, and 40% had not taken any integrated session. About 36% had not taken any attitude, ethics and communication (AETCOM) session, and 30% considered that they were not sufficiently competent. About 68% believed that early clinical exposure (ECE) given is insufficient. "Skills" (50%) and "attitude-communication" (34%) could not be satisfactorily assessed. About 72% believed that the coronavirus disease 2019 (COVID-19) pandemic significantly affected academics, 20% are still confused about the complexities of CBME, and 58% believed they are better prepared for the future. The COVID-19 pandemic (78%), lack of proper training (70%), and adequate faculty (60%) were common difficulties. Frequent hands-on workshops (68%) and better inter-departmental coordination (68%) were suggested. CONCLUSION: First professional-year faculties are slowly getting accustomed to the transition from a traditional to a competency-based curriculum. These reforms are complex, and the challenges need to be addressed sincerely and timely.